2005
DOI: 10.1016/j.cardiores.2004.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor attenuates early ventricular expansion after experimental myocardial infarction

Abstract: G-CSF treatment improves early post-infarct ventricular expansion through promotion of reparative collagen synthesis in the infarcted area, suggesting some beneficial effect of G-CSF on the infarct healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 50 publications
5
87
0
1
Order By: Relevance
“…We previously reported that G-CSF treatment improved (22) and GM-CSF induction aggravated (23) early LV remodeling after MI through modification of the infarct healing process. GM-CSF induces differentiation from immature DC to myeloid DC, with a subsequent increase in Th1 cells, whereas G-CSF induces plasmacytoid DC followed by proliferation of Th2 cells (24 -26).…”
Section: Eft Ventricular (Lv)mentioning
confidence: 96%
“…We previously reported that G-CSF treatment improved (22) and GM-CSF induction aggravated (23) early LV remodeling after MI through modification of the infarct healing process. GM-CSF induces differentiation from immature DC to myeloid DC, with a subsequent increase in Th1 cells, whereas G-CSF induces plasmacytoid DC followed by proliferation of Th2 cells (24 -26).…”
Section: Eft Ventricular (Lv)mentioning
confidence: 96%
“…Orlic and colleagues reported that a significant accelerated mobilization of BMSCs occurs after SCF + G-CSF administration resulting in enhanced myocardial regeneration in infarcted murine hearts [8]. The latter investigations have instead proposed myocardial protection of G-CSF through angiogenesis [9] and prevention of scar formation in the left ventricles (LV) [10,11]. It has been reported that BMSCs secrete a wide array of cytokines which may protect target cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Известно, что структура наполнения желудочков сердца зависит от способности миокарда рассла-бляться и растягиваться, от камерной жесткости, механических факторов -величины градиента дав-ления между предсердиями и желудочками, силой сокращения предсердий, от величины давления в предсердиях, величины КДД в желудочках [2,5,9,11,12]. При ИМ нарушение структуры наполнения идет за счет замедления расслабления в сочетании со снижением растяжимости как следствие зон ише-мии миокарда, приводящей как к замедленному уда-лению кальция из миофибрилл, так и снижению содержания АТФ.…”
Section: результаты и обсуждениеunclassified